Ammonium Hexafluorosilicate (AHFS) Modified HMCM‐22 As Efficient Catalysts for Alkylation of Phenol with Methanol. Issue 45 (5th December 2022) - Liu, Zonghui; Xie, Dehua; Ran, Jianzhou; Wu, Jing; Liu, Na; Xue, Bing
Abstract: A series of x AHFS/HMCM‐22 ( x denotes the amount of AHFS treatment on HMCM‐22, AHFS is the abbreviation for ammonium hexafluorosilicate) were prepared and evaluated in the catalytic synthesis of p ‐cresol by alkylation of phenol with methanol. Several characterization techniques including N2 adsorption‐desorption, XRD, FT‐IR, 27 Al MAS NMR, Pyridine‐IR, and NH3 ‐TPD have been used to analyze the physicochemical properties of the x AHFS/HMCM‐22 catalyst. The conversion of phenol decreased with increasing x of x AHFS/HMCM‐22 catalyst; while the selectivity for p ‐cresol maximized at x=0.07. The 0.07AHFS/HMCM‐22 catalyst was identified as the most efficient catalyst, showing the highest p ‐cresol selectivity (53.3 %) for longer than 24 h under optimized reaction conditions (325 °C, WHSV=2 h −1 ), which is much higher than that of parent HMCM‐22 catalyst (37.1 %). The high p ‐cresol selectivity of the catalyst is attributed to AHFS removing part of the acid sites on the external surface of the HMCM‐22, and preserving the acid sites in the micropores of zeolite. By contrast, the decrease in catalyst activity is due to the decrease in total acid sites. Abstract : HMCM‐22 treated with AHFS is an efficient and stable catalyst for alkylation of phenol with methanol. The selectivity of p ‐cresol is as high as 53.3 % over 0.07AHFS/HMCM‐22, which is much higher than that of parent HMCM‐22 (33.9 %).